A survey of recoverable distributed shared virtual memory systems - Morin, C.; Puaut, I. (IEEE transactions on parallel and distributed systems, 1997)
Distributed Shared Virtual Memory (DSVM) systems provide a shared memory abstraction on distributed memory architectures. Such systems ease parallel application programming because the shared-memory programming model is often more natural than the message-passing paradigm. However, the probability of failure of a DSVM increases with the number of sites. Thus, fault tolerance mechanisms must be implemented in order to allow processes to continue their execution in the event of a failure. This paper gives an overview of recoverable DSVMs (RDSVMs) that provide a checkpointing mechanism to restart parallel computations in the event of a site failure.